Leveraging TikTok to Enhance English Speaking Skills among EFL Students - Zahratul Fitri Annapis, Zahratul Fitri Annapis (Journal of Educational Studies, 2024)
This study explores the potential of the TikTok application as an educational tool to improve English speaking skills among EFL (English as a Foreign Language) students. TikTok’s immense popularity among youth, combined with its short video format and creative features, provides an engaging platform for interactive learning. The research employed a mixed-methods approach, combining qualitative and quantitative techniques to assess the impact of TikTok on speaking proficiency, vocabulary acquisition, fluency, pronunciation, and overall learning motivation. Fifty EFL students participated in the study, which involved pre-tests, post-tests, video assignments, and surveys. Results indicated a significant improvement in speaking skills, with students demonstrating enhanced vocabulary, better pronunciation, and increased confidence in communication. Additionally, the app’s entertaining and user-friendly nature helped reduce language anxiety and foster creativity. The findings underscore TikTok’s potential as a supplementary tool in language education, particularly for fostering engagement and motivation in learning environments. Despite some challenges, such as content curation and managing screen time, TikTok offers a promising avenue for modernizing language instruction and enhancing learner outcomes.